The annexation of the 6 surrounding municipalities to bogotá in 1954. “a prior fact” (2005)
The annexation of the six surrounding municipalities to Bogotá in 1954, was an urban, political and economic process initiated by the middle of the XIX century, and continued along the XX century. The purpose of this annexation was to reaffirm Bogotá as the capital of Colombia, and keep it out of the ordinary municipal regime ruling the rest of the other municipalities, which allowed Bogotá to enlarge its territory. This will be developed by the urbanization process carried out over the final decades of the XX Century. In this article we will conclude that each change of political ideas basically implies a modification in the territory, and also in the way the decisions are made.